The algebraic representation of the statement is x + x² - yz = 0
<h3>What are algebraic expressions?</h3>
Algebraic expressions brings the idea of creating or expressing numbers using letters or alphabets without specifying their actual values.
From the information given , we have that;
- sum of x and it's square = x + x²
- Equal to y × z
Now, let's equate the expressions;
x + x² = y × z
x + x ² = yz
Let's make into quadratic form
x + x² - yz = 0
Thus, the algebraic representation of the statement is x + x² - yz = 0
Learn more about algebraic expressions here:
brainly.com/question/723406
#SPJ1
the value would be 2x10^7
Answer:
r = 7 q - 34
Step-by-step explanation:
Solve for r:
-34 + 7 q - r = 0
Subtract 7 q - 34 from both sides:
-r = 34 - 7 q
Multiply both sides by -1:
Answer: r = 7 q - 34
Let x be the number. x= 2x-17
-x=-17
x=17
Answer:
I will tell you.
Step-by-step explanation:
a.-13
b.13
c.-25
d.25
e.20
f.-6
g.-22
h.-72